2013
DOI: 10.1016/j.cognition.2013.02.018
|View full text |Cite
|
Sign up to set email alerts
|

On the problem-size effect in small additions: Can we really discard any counting-based account?

Abstract: a b s t r a c tThe problem-size effect in simple additions, that is the increase in response times (RTs) and error rates with the size of the operands, is one of the most robust effects in cognitive arithmetic. Current accounts focus on factors that could affect speed of retrieval of the answers from long-term memory such as the occurrence of interference in a memory network or the strength of memory traces that would differ from problem to problem. The present study analyses chronometric data from a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
141
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(158 citation statements)
references
References 26 publications
16
141
1
Order By: Relevance
“…The hypothesis of automated procedures was reinforced by a recent study in which we had adult participants solving very small additions with operands varying from 1 to 4 (Barrouillet & Thevenot, 2013). This study revealed a quasi perfect monotonic size effect in non-tie problems, with RTs increasing with the size of both the first and the second operand (mean slopes of 16 ms and 23 ms respectively).…”
Section: Recent Evidence For a Problem-size Effect Due To Counting Stmentioning
confidence: 64%
See 4 more Smart Citations
“…The hypothesis of automated procedures was reinforced by a recent study in which we had adult participants solving very small additions with operands varying from 1 to 4 (Barrouillet & Thevenot, 2013). This study revealed a quasi perfect monotonic size effect in non-tie problems, with RTs increasing with the size of both the first and the second operand (mean slopes of 16 ms and 23 ms respectively).…”
Section: Recent Evidence For a Problem-size Effect Due To Counting Stmentioning
confidence: 64%
“…It is also difficult to account for by a hypothesis of exposure frequency. As we noted in Barrouillet and Thevenot (2013), the potential effect of differences in frequency has probably been overestimated in accounting for retrieval times in the domain of mental arithmetic. In the linguistic domain, dramatic differences in word frequency (from about 3000 to 60 per million) result in rather small differences in RTs (i.e., 15 ms in a lexical decision task, Ferrand et al, 2011), whereas the observed difference in RTs between probably very frequent additions such as 2 + 1 and 2 + 4 was higher than 90 ms.…”
Section: Recent Evidence For a Problem-size Effect Due To Counting Stmentioning
confidence: 99%
See 3 more Smart Citations